Dielectric Studies of PEO-based Polymer Electrolytes Doped with LiTFSI Salt and EMIMTFSI Ionic Liquid - Hayati Al-Madihah Hashim, Nor; Hanum Yahaya Subban, Ri (International Journal of Engineering and Technology, 2019)
In this work, poly (ethylene oxide) (PEO) is doped with Lithium bis (trifluoromethanesulfonyl) imide (LiTFSI) salt and 1-Ethyl-3-methylimidazolium bis (trifluromethanesulfonyl) imide (EMIm-TFSI) ionic liquid, a plasticiser, for preparation of PEO-LiTFSI-EMImTFSI plasticised polymer electrolyte (PPE) system. Impedance spectroscopy is used to analyse the dependence of dielectric behaviour of the films on frequency and temperature. It is performed in the temperature range between 303K to 343K for frequencies between 50 Hz to 1 MHz. The cationic transport in the films may be explained from the dielectric constant, Ô‘r and dielectric loss, Ô‘i where they are found to increase with temperature at lower frequency and decrease at higher frequency, showing that the electrodes were being polarized. Both real parts, Mr and imaginary part, Mi of the modulus showed an increase at high frequency that indicates the spread of conductivity relaxation. The highest temperature (343K) achieved the lowest relaxation time, Ï„ due to increase in number of ions and increase in mobility of ions in the polymer system indicating that conductivity in this system is thermally activated.Â